Problem Based Learning Solutions to Improve Student Learning Outcomes - Rivaldo, Rivaldo; Ridha, Arif (Ahlussunnah: Journal of Islamic Education, 2024)
The implementation of Islamic Religious Education learning in the eleventh grade of State Senior High School One, Empat Koto District, Agam Regency, shows that teachers have not developed an appropriate learning model, and the teaching modules used are not yet appropriate to the learning process in the classroom, resulting in low student learning outcomes. This study aims to analyze the effectiveness of the application of problem-based learning models in improving student learning outcomes in Islamic Religious Education subjects. This study is a classroom action research that uses qualitative and quantitative approaches. Learning planning is carried out by reviewing learning outcomes, compiling learning objectives, preparing media and learning resources, and compiling student worksheets, evaluation questions, and observation sheets. The implementation of learning follows the stages of the problem-based learning model, namely problem recognition, organizing learning activities, guiding the investigation process, presenting results, and evaluating the problem-solving process. Learning evaluation is carried out in two cycles. In the first cycle, the first meeting, the results are in the sufficient category; the first cycle, the second meeting, increases to the good category; and in the second cycle, the first meeting, the learning outcomes are in the very good category. These results indicate that the application of the problem-based learning model is effective in improving student learning outcomes in Islamic Religious Education subjects.